Penser le bilan et le devenir de l’histoire du temps présent. Une approche des pratiques en études germaniques et dans l’hispanisme en France - Coignard, Tristan; Sarría Buil, Aránzazu (Historiografías, 2021)
The paper has two complementary aims. Starting from the fact that the “history of the present” and its methods have been institutionalized especially in France, it deals, on the one hand, with the debates that these historiographical practices have aroused both at the end of the twentieth and during the early twentieth-first centuries. In this way, the article points out to the challenges that “historians of the present” are currently facing, particularly in a context of strong social claims related to the globalized awareness of historical memory. On the other hand, the authors examine the potential contributions of areal studies to the further development of the “history of the present”, by highlighting its implications in the fields of German studies and Hispanism in France.Key wordsHistory of the Present, German Studies, Hispanism, France, civilization.